Reflections on Political Islam - Nancy A. Khalil (International Institute of Islamic Thought, 2016)
The International Institute of Islamic Thought (IIIT) participated in the annual meeting of the American Academy of Religion (AAR) in Atlanta, GA, held November 21-24, 2015. In addition to the participation of staff and associates in several meeting events and panels, IIIT maintained a book booth in the Exhibit Hall, co-organized a panel on “Opportunities and Challenges of Teaching Islamic Studies in Theological Seminaries,” and held its second annual AAR Reception and Special Lecture. Offering a tribute to Ismail al-Faruqi (d. 1986), IIIT co-founder and cofounder of the AAR’s “Study of Islam” section, Abubaker Alshingieti (executive director, IIIT) and Ermin Sinanović (director of research, IIIT) expressed great pride in rekindling a stronger IIIT presence at the AAR by reviving the historical link established by al-Faruqi. Fittingly, John Esposito (Georgetown University), al-Faruqi’s first doctoral advisee, delivered the keynote speech: “Reflections on Political Islam: Concepts and Contexts.” An intellectual giant in his own right, Esposito presented a historical analysis of the rise of political Islam movements during the latter half of the twentieth century through his individual interactions, appointments, and presence in spaces of influence at critical times. His keynote speech served both as an intellectual analysis as well as a personal journey, full of spontaneously sprinkled firsthand stories and narratives from private conversations. He emphasized the critical need to avoid ahistoric analyses of such movements and to resist symptomatic treatments that have become a popular approach by western governments blind to their own roles in such undesired behaviors and violence. Referring to challenges like ISIS and youth radicalization, Esposito stated that “unless you understand the context within which political Islam arose...: who were the players, what were the issues for these movements, and also what their interactions were with government, you can’t understand why we continue to screw up today.” Making specific reference to recent government initiatives on Countering Violent Extremism that are youth-centric and target the great role religion occupies in people’s lives, he reminded the audience that discounting a history of oppression by western-backed authoritarian regimes is a myopic perspective to the rise of radicalism. His speech spanned over fifty years of political history and American involvement in Muslim-majority nations with an emphasis on the Iranian ...